Some properties of the nickel-containing hydrogenase of chemolithotrophically grown Rhizobium japonicum. - Harker, A R (1984)
The uptake hydrogenase of chemolithotrophically grown Rhizobium japonicum was purified to apparent homogeneity with a final specific activity of 69 mumol of H2 oxidized per min per mg of protein. The procedure included Triton extraction of broken membranes and DEAE-cellulose and Sephacryl S-200 chromatographies. The purified protein contained two polypeptides separable only by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. They comigrated on native polyacrylamide gels and sucrose density gradients. The molecular weights were ca. 60,000 and 30,000. Densitometric scans of the sodium dodecyl sulfate gels indicated a molar ratio of 1.03 +/- 0.03. Antiserum was developed against the 60-kilodalton polypeptide for use in hydrogenase detection by an enzyme-linked immunosorbent assay. The antiserum did not cross-react with the 30-kilodalton polypeptide. Native gel electrophoresis of Triton-extracted cells grown in the presence of 63Ni showed comigration of the hydrogenase and radioactive Ni.